Mapping the landscape: Growth and trends in ethnomathematics research – A bibliometric review - Noerhasmalina, Noerhasmalina; Hidayatulloh, Hidayatulloh (Universitas Islam Raden Intan Lampung, INDONESIA, 2023)
Background: At the junction of mathematical tenets and cultural paradigms, ethnomathematics has begun to manifest its scholarly presence, exhibiting a progression marked by sporadic volatility but generally steering towards a positive direction.Aim: This bibliometric survey meticulously delineates the ethnomathematics-related publication portfolio, unearths influential scientific platforms, and spotlights the foremost contributors in the field.Method: Harnessing the capabilities of VOSviewer software, this investigation excavates the wealth of knowledge embedded within the associated articles and documents. The probe utilized the keyword